Modal Sosial Petani Dan Produktivitas Kelapa Di Desa Sea Kecamatan Pineleng Kabupaten Minahasa - Vira Ranna Dien; Noortje M. Benu; Martha M. Sendow (AGRI-SOSIOEKONOMI, 2022)
This study aims to examine the social capital of farmers and coconut productivity in Sea Village, Pineleng District, Minahasa Regency. This research was conducted from July 2021 to April 2022. The data used were primary data and secondary data. Primary data were collected through interviews, based on a questionnaire. Secondary data was obtained from the Sea Village office in the form of geographical conditions and socio-economic conditions of the community. The sample of this study were 30 farmers from a total population of 60 coconut farmers who were taken using purposive sampling method. The results showed that the social capital of coconut farmers in Sea Village, Pineleng District, Minahasa Regency was relatively high, based on the results of the study with an index of 75.86% and the tendency of productivity variables in the medium category with a percentage of 43.33% or as many as 13 coconut farmers.